Crash Helmet Types, Usage and Safety Implications for Student Motorcyclists in the Wa Municipality, Ghana - Marfo, Samuel; Akpade, Joshua; Musah, Halidu (Ghana Journal of Higher Education Management, 2024)
Across the globe, crash helmets are promoted as the most effective protective gear against head injuries and preventable deaths. Although crash helmets offer protection to users, their degree of protection vary according to the types, namely Full- face, Open- face or Half- face. Apparently, among crash helmet related studies that provide information on the relevance of helmets to riders, there is little information on helmet types and their safety implications in Ghana. Against this background, 78 student motorcyclists from three tertiary institutions and two key informants in the Wa Municipality were selected through quota and purposive sampling techniques in a qualitative research design. Primary data gathered through interviews revealed that 41% of student helmet users are less likely to suffer preventable deaths and injuries from motor crashes due to the use of the Full- face crash helmets which are deemed the most effective and globally recommended helmets. The relative low patronage of the Full-face helmets requires periodic educational campaigns by management and student leadership of tertiary institutions, the Motor Traffic and Transport Department of the Ghana Police Service and the Ghana National Road Safety Commission to orient student motorcyclists about the dangers of not wearing the Full-face helmets.